(3eLehYI aj GdgfOSIs - (3GjSbdGhSs ((3YHO GdQMef Hf Ydi s)
(3ChdgG (B:s
(3gPG cJGH GSJdGhS ai GdeWGdY eeG CUdMI hGdcfOi gh bSWG Hf dhbG GdHYdHci hgh eTJed Ydi KdGK ebOeGJ s
(3BNQgG (B:s
(3aEPG YQafG eWGdY GdLRA cGfJ GdRjGOGJ eYdheI aWGdY LejY GdCLRGA eYdheI hPdc eG CQOfGg hbY JJeje GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1459s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdQjGVjGJs